Civil liability of credit rating agencies: Regulatory all-or-nothing approaches between immunity and over-deterrence - Brigitte Haar (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
The European Commission recently put forward a proposal for a regulation to amend and strengthen the 2009 version of the EU's rules on the regulation of credit rating agencies (CRA3). Among other things, Art. 35a of the draft proposal introduces strict liability for rating agencies. This liability proposal is at odds with the aim to strengthen competition in the rating sector and could have a chilling effect on capital markets. The paper analyses existing rules on civil liability of rating agencies under different legal systems. Subsequently, the provision under Art. 35a of the Draft Proposal is examinded more closely. Suggestions on possible improvemts of the proposal are made.
urn:nbn:de:hebis:30:3-297348
Keywords: 330; CRA3; Rating Agencies; contractual liability; regulation